The optimisation of chromatographic conditions for the determination of acceptor-donor properties of graphene oxide and reduced graphene oxide - Henryk Grajek; Justyna Jonik; Leszek Rutkowski; Marcin Purchała; Tomasz Wawer (ACTA INNOVATIONS, 2018)
The oxidised and reduced graphene samples (having different surface functionalities) were studied by inverse gas chromatography to characterise their acceptor-donor properties. The DN values denoting the donor number in the Gutmann scale and the AN* values denoting the acceptor number in the Riddle-Fowkes scale have been chosen in the estimation of the electron-acceptor parameter KA and electron-donor parameter KD values.